Levels of hope among children under 18 years old with acute lymphoblastic leukemia undergoing chemotherapy: A descriptive study - Fania Putri Alya; Diana Ulfah; Eli Lusiani; Kiki Deniati; Rona Febriyona; Firman Sugiharto; Siti Rissaadah (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Hope is an essential psychological resource that enables children with cancer to cope with the stress and uncertainty of long-term treatment. However, research focusing on the level of hope among children with Acute Lymphoblastic Leukemia (ALL) in Indonesia or Southeast Asia remains limited, as most studies have centered on adults or on depression and anxiety rather than hope. Understanding hope among pediatric cancer patients is crucial for developing psychosocial interventions that enhance emotional resilience and treatment adherence. Purpose: to describe the levels of hope among children under 18 years old with ALL who were undergoing chemotherapy. Method: This was a quantitative descriptive study involving 66 respondents selected through convenience sampling. Data were collected using the Children’s Hope Scale (CHS), consisting of six items that assess agency and pathway thinking. Ethical approval and parental consent were obtained prior to data collection. Descriptive statistics were applied to analyze respondents’ demographic characteristics and hope scores. Result: The findings showed that most respondents were aged 8–12 years (56.1%), male (59.1%), and diagnosed with high-risk ALL (89.4%). More than half (54.5%) demonstrated a high level of hope, while 45.5% had a low level of hope. Younger children exhibited higher hope levels compared to adolescents. The mean hope score was 22.9 ± 3.95, with a median of 23 and a score range of 16–32, indicating a moderate to high overall level of hope. Conclusion: Most children with ALL in this study maintained a moderate to high level of hope during chemotherapy. These results emphasize the importance of assessing hope as part of psychosocial care. Strengthening hope through supportive communication and family-centered interventions can enhance children’s PWB and promote better adherence throughout the treatment process.